(untitled) (Bioagro, 2020)
The use of irrigation is essential to increase crop productivity; however, for efficient water management, it is necessary to more accurately estimate soil moisture. For this reason, the objective in this work was to calibrate FDR model 10HS frequency domain reflectometry sensors (Decagon Devices) for use in a Geric Xanthic Ferralsol type soil. For the calibration, non disturbed soil samples were collected in PVC pipes at two depths (0-20 and 20-40 cm), with four repetitions each and they were placed in trays with distilled water until saturation. Subsequently the sensors were introduced in the sample to obtain the moisture at the saturation point. Then, the samples were placed in an oven at 60 ºC, until they reached approximately 10 % humidity. The results showed that the gross volumetric moisture data recorded before calibration did not coincide with the 1:1 line, presenting divergent behavior, thus demonstrating the need for calibration. According to the results, it is concluded that the equations generated with the data before the calibration overestimated the volumetric soil moisture, and the equations obtained after the calibration satisfactorily measure the moisture of the Geric Xanthic Ferralsol type soil.